Self‐Synthesizing Nanorods from Dynamic Combinatorial Libraries against Drug Resistant Cancer. Issue 6 (16th December 2020) - Cao, Yu; Yang, Jian; Eichin, Dominik; Zhao, Fangzhe; Qi, Dawei; Kahari, Laura; Jia, Chunman; Peurla, Markus; Rosenholm, Jessica M.; Zhao, Zhao; Jalkanen, Sirpa; Li, Jianwei
Abstract: Molecular self‐assembly has been widely used to develop nanocarriers for drug delivery. However, most of them have unsatisfactory drug loading capacity (DLC) and the dilemma between stimuli‐responsiveness and stability, stagnating their translational process. Herein, we overcame these drawbacks using dynamic combinatorial chemistry. A carrier molecule was spontaneously and quantitatively synthesized, aided by co‐self‐assembly with a template molecule and an anti‐cancer drug doxorubicin (DOX) from a dynamic combinatorial library that was operated by disulfide exchange under thermodynamic control. The highly selective synthesis guaranteed a stable yet pH‐ and redox‐ responsive nanocarrier with a maximized DLC of 40.1 % and an enhanced drug potency to fight DOX resistance in vitro and in vivo. Our findings suggested that harnessing the interplay between synthesis and self‐assembly in complex chemical systems could yield functional nanomaterials for advanced applications. Abstract : Dynamic combinatorial chemistry was employed to explore an ideal carrier molecule for anti‐cancer drug delivery. Driven by thermodynamics, the carrier molecule was quantitatively yielded by its co‐self‐assembly with a template and a drug doxorubicin (DOX). The self‐assembled nanocarrier with a drug‐loading content of 40 % was stable yet pH‐ and redox‐responsive and could enhance drug potency and eliminate DOX‐resistant cancer in vivo in 13 days.